Evaluating the Embedding of Games Based Learning in a Computing Subject at University - Todorova, Emilia; Moffat, David (European conference on games based learning, 2013)
Games Based Learning (GBL) has been an interest area for research in the education sector for the past few years. Current research has been seen to affect secondary and primary education systems, but GBL has rarely been seen on a Higher Education (HE) level. Furthermore, although the case for using games has been built through research in Serious Games, the actual integration of GBL in curricula is under researched at the moment. As part of a research project in Glasgow Caledonian University, a module within the Games Development and Design Suite was introduced to a game in order to measure the improvement of their skills and subject knowledge. As part of the research, the integration of the GBL method was also analysed in terms of its success and ease of embedding to the other teaching and learning techniques used. In terms of the modules used for the study, it can also be determined what can make the integration work better and what should be avoided if GBL is used in the Higher Education classroom